HUBUNGAN MAKANAN SIAP SAJI (FAST FOOD) DENGAN KEJADIAN STATUS GIZI PADA REMAJA SMP NEGERI 1 GADING REJO TAHUN 2021 - Nia Agustina Saputri Khairul Anam; Riska Nur Suci Ayu; Desti Ambar Wati; Amali Rica Pratiwi (Sekolah Tinggi Ilmu Kesehatan Holistik, 2022)
Background: Adolescence is a period where it is easy to be influenced by the envronment and close friend, the influence of friend will influence the changes in adolecent eating and will like new things such as fast food that contains high energy, fat, and sodium, thus making adolescents experience nutritional status problems. Objective: The purpose of this study was to determinne whether there is a corelation between ready to eat food and the incidence of nutritional status in adolescents SMP Negeri 1 Gading Rejo Tahun 2021. Method: The design used in this research is quantitavie using cross sectional method. Sampling is done using techniques random sampling the sampel is study amounted to 152 person.data analysis in this study using ujichi-square and uji fisher. Results: The results of this study obtained obesity 12 (7,9%), overweight 47 (30,9%), thin 22 (14,5%), an normal 98 (64,5%). Teenagers who often eat fast food 113 (74,3%). There is a corelation between fast food and the incidence of nutritional status in teenagers with p value 0,000. Conclusion: There is a corelation between fast food and the incidence of nutritional status in teenagers SMP Negeri 1 Gading Rejo.